Cairo declaration of human rights: viability as an Islamic alternative - Haneef, Sayed Sikandar Shah (IIUM Press, 2016)
The Official Islamic Declaration of Human Rights, namely Cairo Declaration has become a subject of debate among Muslim academia as far as its viability to serve as an alternative to the UN declaration of human rights. This section argues either for its empowerment or its replacement by a more workable alternative within the constraints of Muslim nation states.